PS1 - 188 Rehabilitation Consultation: An Integrated Model for Addressing Rehabilitation Concerns in the Primary Brain Tumor Population. (18th October 2016) - Lax, I.; Daniels, M.; Kanter, C.; Mason, W.; Edelstein, K.
Abstract : Individuals with primary brain tumors experience a range of physical, cognitive and psychosocial sequelae which impact their independence, safety and quality of life. These impairments may be addressed through rehabilitation intervention. Despite acknowledgement that timely rehabilitation services over the course of the disease process is of benefit, few outpatient neuro-oncology treatment teams include a rehabilitation professional. Purpose: The aims are: (1) to describe a rehabilitation consultation model of care integrated into outpatient neuro-oncology treatment for individuals with primary brain tumors; and (2) to describe the characteristics of individuals referred for rehabilitation services. Methods: This retrospective descriptive study examined data from 200 individuals that received rehabilitation consultation from January 2015 to March 2016 at Princess Margaret Hospital, Pencer Brain Tumor Centre. Information on patient demographics, referral characteristics, and number of patient care visits was collected. Descriptive statistics were calculated. Preliminary Results: Of all patients, (n=195), the most common diagnosis is glioblastoma, 39% (n=76), and 50% are 50-69 years of age (M=55, SD=15.0). The most common reason for initial referral was decline in physical functioning, strength and balance (41%). In 77% of cases, patients were seen immediately at the time of referral. In total, 540 consultations were completed (face-to-face=230, telephone=310) with 2.78 on average (SD=4.0) per patient. Conclusion: Given the range of symptoms that individuals with primary brain tumors experience coupled with changes in functional status as the disease progresses, integrated and timely rehabilitation consultation is feasible.